Treatment of fracture subluxations of the proximal interphalangeal joint using a ligamentotaxis device: a multidisciplinary approach. (October 2015) - MacFarlane, R. J.; Gillespie, S.; Cashin, F.; Mahmood, A.; Cheung, G.; Brown, D. J.
Complex fracture subluxations of the proximal interphalangeal joint are often difficult to treat and their outcome variable. A number of methods for treatment of these injuries have been described. We have used a ligamentotaxis device ( Ligamentotaxor, Arex, Palaiseau Cedex, France) since 2008. We performed 28 operations in 28 patients with complex proximal interphalangeal joint injuries over a 3-year period. Patients followed a standardized postoperative rehabilitation regime, including fixator adjustment as necessary. The mean age was 33 years (range 18–67). The mean time to surgery was 7 days. At final follow-up (mean 22 months, range 6–52) the mean proximal interphalangeal joint range of motion was 85° (range 60°–110°). The mean QuickDASH functional outcome score was 4.8 (range 0–36.4). Our results compare favourably with other devices reported in the literature.